Force feedback without sensor : a preliminary study on haptic modeling - Sun, Zhenglong (2013)
Haptic feedback is an active trend in robotic surgery. However, it is not always feasible to place physical force sensors on the robotic tool-tips due to size or other constraints. Haptic modeling of the organ/tissue could be an alternative approach to provide estimated force information from available data. In this paper, we investigate haptic modeling to provide real-time force estimation in endoscopic surgery. Viscoelastic behavior of the gastrointestinal organ/tissue needs to be taken into consideration. Hence, we proposed a modified haptic model based on commonly-used lumped models, in order to restore the tool-tissue interaction force by using the robot motion. Performance of this approach was evaluated by ex-vivo experiments. The proposed model is capable of approximating the interaction force. Discussions were made on possible limitations and problems in the implementation of such approach.